(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The primary objective of this study is to assess the performance of Saudi banks over a specified period, which is from 2015 to 2021. The chosen methodology for this analysis is panel data regression. Panel data combines cross-sectional and time-series data, making it suitable for examining trends and relationships over time among different entities (in this case, banks). The study uses annual financial data for the 10 selected banks over the seven-year period, from 2015 to 2021. The study finds a marginally negative association between COVID-19 and the performance indicators ROA and ROE. This suggests that the COVID-19 pandemic had a slightly adverse impact on the profitability and equity returns of the Saudi banks included in the analysis. The study employs a dummy variable, likely called "COVID," to account for the impact of the COVID-19 pandemic. The results indicate that there is a statistically significant but weakly negative association between return on equity (ROE) and credit risk (CR). The study finds that credit risk and liquidity risk are both insignificant when analyzing return on assets (ROA). These findings provide valuable insights into how external factors like a pandemic and internal factors like credit risk can affect the financial performance of banks. The study’s results offer regulatory authorities in Saudi Arabia a valuable resource for making informed decisions regarding the financial performance and stability of the banking sector during a crisis. By incorporating these findings into their policies and oversight activities, regulatory bodies can contribute to a healthier and more robust banking system that benefits both the financial institutions and the broader economy.